Analysis of Fraudulent Financial Reporting Using the Fraud Triangle (Study Case: PT Tiga Pilar Sejahtera Tbk) - Maulida Salmi Utie; Siti Nurwahyuningsih Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze PT Tiga Pilar Sejahtera Food Tbk (AISA)’s fraudulent financial reporting (FFR) in relation to the fraud triangle theory. This study uses a quantitative approach by analyzing secondary data obtained from AISA's financial statements during 2003-2017. The analysis will be carried out using Excel software to produce regression and variable correlation analyses. The research method uses the Beneish M-score model as FFR proxy and SAS No.99 fraud risk factor as fraud triangle proxies (pressure, opportunity, rationalization). The test results show that pressure, opportunity, and rationalization significantly influence AISA's scandal. The pressure factor is measured by financial target and external pressure indicators. The nature of industry indicator measures the opportunity factor, and the audit reports indicator measures the rationalization factor.